The Effect of Compensation, Workload, and Work Discipline on Employee Performance - Farhan Ali Ash Shidqy; Sri Susilowati (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to analyze the effect of compensation, workload, and work discipline on employee performance at the Hajj Document Section of the Ministry of Religious Affairs, East Java Province. A quantitative approach was employed, with primary data collected from 30 employees (saturated sample) using a Google Form questionnaire. Multiple linear regression analysis with SPSS Version 26 was applied. The results show that compensation, workload, and work discipline have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) is 63.9%. The main implication is that fair compensation, manageable workload, and high discipline improve employee performance. A limitation is the small sample size from a single section.